ISOLASI DAN KARAKTERISASI EKSTRAK KULIT JENGKOL (Pithecellobium jiringa) SEBAGAI INHIBITOR ENZIM PENYAKIT MALARIA Plasmodium falciparum MALATE QUINONE OXIDOREDUCTASE - Rhamal Amir; Chaidir Chaidir; Aden Dhana Rizkita; Anis Herliyanti (Universitas Wahid Hasyim Semarang, 2022)
In order to discover and identify antimalarial active compounds, jengkol peel extract was isolated and tested for antimalarial activity. This study aims to determine the antimalarial active compound from jengkol peel extract which functions as an inhibitor of the Malate Quinone Oxidoreductase (MQO) enzyme. In this study, the extraction process was carried out using methanol as a solvent with the maceration method. The maceration results were then concentrated using a rotary evaporator with low pressure at a temperature of 40-45°C to obtain a Crude extract of 203 grams. Then liquid-liquid fractionation was carried out with four types of solvents, namely n-hexane, ethyl acetate, methanol, and water according to the level of polarity. Each fraction obtained was 400 ml which was then tested for enzyme inhibition using the MQO enzyme formation inhibition method. The fraction that had the highest inhibitory activity was the ethyl acetate fraction of 80%. Confirmation was done again with the same separation using column chromatography so as to produce the ethyl acetate fraction which was confirmed to be identified using HPLC producing peaks at retention times of 22 and 23 minutes. The results showed that in jengkol peel extract there were active compounds that acted as inhibitors of the MQO enzyme but further tests were needed to confirm these peak compounds.